Emergencies: on the misuse of government powers - Christian Bjørnskov; Stefan Voigt (Public Choice, 2021)
Nine out of 10 constitutions contain explicit emergency provisions, intended to help governments cope with extraordinary events that endanger many people or the existence of the state. We ask two questions: (1) does the constitutionalization of emergency provisions help governments to cope with disasters and other extraordinary events? (2) What particular parts of emergency constitutions fare best? We find that the more advantages emergency constitutions confer to the executive, the higher the number of people killed as a consequence of a natural disaster, controlling for its severity. As this is an unexpected result, we discuss a number of potential explanations, the most plausible being that governments use natural disasters as a pretext to enhance their power. Furthermore, the easier it is to call a state of emergency, the larger the negative effects on basic human rights. Interestingly, presidential democracies are better able to cope with natural disasters than parliamentary ones in terms of lives saved, whereas autocracies do significantly worse in the sense that empowerment rights seriously suffer in the aftermath of a disaster.
Keywords: K40; Z13; 330; Constitutional emergency provisions; State of emergency; État de siege; Regime transformation; Positive constitutional economics